Twelve-month mortality and functional outcomes in hip fracture patients under 65 years of age. Issue 10 (October 2016) - Ekegren, C.L.; Edwards, E.R.; Page, R.; Hau, R.; de Steiger, R.; Bucknill, A.; Liew, S.; Oppy, A.; Gabbe, B.J.
Abstract: Introduction: There has been a recent call for improved functional outcome reporting in younger hip fracture patients. Younger hip fracture patients represent a different population with different functional goals to their older counterparts. Therefore, previous research on mortality and functional outcomes in hip fracture patients may not be generalisable to the younger population. The aims of this study were to report 12-month survival and functional outcomes in hip fracture patients aged <65 years and predictors of functional outcome. Methods: Hip fracture patients aged <65 years (range 17–64) registered by the Victorian Orthopaedic Trauma Outcomes Registry over four years were included and their 12-month survival and functional outcomes (Extended Glasgow Outcome Scale) reported. Ordered multivariable logistic regression was used to identify predictors of higher function. Results: There were 507 patients enrolled in the study and of the 447 patients (88%) with 12-month outcomes, 24 (5%) had died. The majority of patients had no comorbidities or pre-injury disability and were injured via road trauma or low falls. 40% of patients sustained additional injuries to their hip fracture. 23% of patients had fully recovered at 12 months and 39% reported ongoing moderate disability. After adjusting for all key variables, odds of better function 12-months post-fracture were reduced for patients with co-morbidities, previous disability or additional injuries, those receiving compensation or injured via low falls. Conclusions: While 12-month survival rates were satisfactory in hip fracture patients aged under 65 years, their functional outcomes were poor, with less than one quarter having fully recovered 12 months following injury. This study provides new information about which patients may have difficulty returning to their pre-injury level of function. These patients may require additional or more intensive post-discharge care in order to fulfil their functional goals and continue to contribute productively to society.